Implementasi Business Intelligence Pada Analisis Perkembangan Hasil Pertanian Provinsi Sumatera Selatan - Muhammad Danu Riyanda; Suyanto Suyanto (Journal of Computer and Information Systems Ampera, 2020)
In the process of data collection of agricultural food products and horticulture consists of several data covering the time, area, area of land, crop yields, and types of plants stored in the form of files with large amounts of data. The large amount of data can cause errors in compiling information for the process of analysis and evaluation for the agriculture department. The analysis process can be faster and more precise by implementing Business intelligence. Business intelligence is a concept and method for managing and analyzing data and facts into more effective information to improve the quality of organizational evaluation and decision-making processes. One form of information that can be provided from the application of business intelligence is a visual dashboard that can help display information that makes it easier to analyze the development of agricultural products efficiently and interactively. Processing data for analysis in this study using the Pentaho application. By implementing Business Intelligence, it is expected to be able to assist the Department of Food Agriculture and Horticulture in South Sumatra Province in analyzing the development of agricultural products